Sisters' Blended Value Project Phase II (2022–2024): Monitoring, Evaluation, and Learning Report - Aming’a, M.; Ndunge, A.; Njiraini, N.; Njoroge, A.; Kuria, L. (My University, 2025)
This Monitoring, Evaluation, and Learning (MEAL) report presents the outcomes of the Sisters’ Blended Value Project Phase II (2022–2024), implemented by Strathmore University Business School in partnership with ACWECA and funded by the Conrad N. Hilton Foundation. The project aimed to transform Catholic Sisters’ social ministries in Kenya, Uganda, Tanzania, and Zambia into sustainable social enterprises. Key achievements include training 690 Sisters, engaging over 700 in collaborative networks, producing 43 research outputs, and providing seed funding to 61 congregations. Institutional anchors such as the Strathmore Africa Case Centre, Case Book, and Social Entrepreneurship Hub were established to ensure sustainability. The report concludes that the project substantially achieved its objectives, with overall performance rated satisfactory, while highlighting long-term financial resilience as a continuing challenge.
Full text monitoring, evaluation, and learning report for the Sisters' Blended Value Project Phase II (2022–2024).
Keywords: Social entrepreneurship; Catholic Sisters; Sustainable development; Monitoring and evaluation